Contentious activism and political trust in non-democratic regimes: evidence from the MENA. Issue 8 (16th November 2020) - Sika, Nadine
ABSTRACT: This study discusses the relation between political trust and contentious activism in non-democratic regimes, via quantitative and qualitative analysis of three countries in the Middle East and North Africa (MENA), Turkey, Morocco and Tunisia. In this article I add to the debate on repression and dissent, by linking political trust in the coercive apparatus to contentious activism. Are activists more inclined to contest their regimes, when they have low political trust levels, especially in the coercive apparatus? I demonstrate that low political trust, especially in the coercive apparatus prompts contentious activism in non-democratic regimes.